1999
DOI: 10.1098/rspb.1999.0903
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of basal metabolism in breeding female kittiwakes Rissatridactyla

Abstract: We studied kittiwakes (Rissa tridactyla) breeding near Ny-Ðlesund (798 N, 128 E) on Svalbard. In 1997, the basal metabolic rates (BMRs) of 17 breeding females were measured during the incubation and chickrearing periods. The mean body mass of the kittiwakes decreased signi¢cantly (by 10%) between the incubation and chick-rearing periods. At the same time, both the whole-body and mass-speci¢c BMRs decreased signi¢cantly. There was a positive and signi¢cant relationship between the BMR residuals from the incubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 41 publications
3
81
3
Order By: Relevance
“…In several species, including both laboratory and natural populations, BMR or V O2,max remained highly repeatable across much of the life span (Szafranska et al, 2007;Rønning et al, 2005). In others, repeatability declined over time (Chappell et al, 1995;Bech et al, 1999;Hõrak et al, 2002;Vézina and Williams, 2005).…”
Section: Repeatability Of V O2maxmentioning
confidence: 99%
See 1 more Smart Citation
“…In several species, including both laboratory and natural populations, BMR or V O2,max remained highly repeatable across much of the life span (Szafranska et al, 2007;Rønning et al, 2005). In others, repeatability declined over time (Chappell et al, 1995;Bech et al, 1999;Hõrak et al, 2002;Vézina and Williams, 2005).…”
Section: Repeatability Of V O2maxmentioning
confidence: 99%
“…Despite the importance of repeatability for responses to selection, rigorous testing of metabolic rate repeatability (and to a lesser extent, heritability) has become widespread only in the last two decades, with greater emphasis on laboratory-housed animals than on wild populations. In general, these studies have revealed substantial repeatability of the extremes of aerobic metabolism (V O2,max elicited by cold or exercise, and BMR or resting metabolic rate) (Hayes and Chappell, 1990;Chappell et al, 1995;Chappell et al, 1996;Bech et al, 1999;Hayes and O'Connor, 1999;Labocha et al, 2004;Rønning et al, 2005;Szafranska et al, 2007;Evans and Rose, 2010), although repeatability was not found in some species (Swanson and Weinacht, 1997;Russell and Chappell, 2007). In several species, including both laboratory and natural populations, BMR or V O2,max remained highly repeatable across much of the life span (Szafranska et al, 2007;Rønning et al, 2005).…”
Section: Repeatability Of V O2maxmentioning
confidence: 99%
“…How ever, SMR tended to decrease over the two res pi rom e try tri als in all birds from small brood sizes and in females from larger broods, despite a decrease in ambient tem per a ture, which would nor mally be asso ci ated with an increase in met a bolic rate (Gav ri lov, 1996). Whilst sev eral stud ies have shown that rest ing metab o lism is highly repeat able in avian spe cies (Bech et al, 1999;Ron ning et al, 2005; Vez in a and Williams, 2005), they have not yet com pared metab o lism dur ing the nest ling stage with later stages of devel op ment. In this study SMR com par i sons between the two met a bolic tri als revealed non-signifi cant repeat abil ity in both of our met a bolic param e ters (SMR: F 43,44 = 0.84, p = 0.72; sd: F 43,44 = 1.17, p = 0.30).…”
Section: Long Term Effects On Metab O Lismmentioning
confidence: 99%
“…Recent evidence suggests that intraspecific variation in resting MR has a strong genetic component (Wikelski et al 2003;Ksiazek et al 2004). Nevertheless, resting MR is a plastic character that not only varies among populations, but also at an individual level (Bech et al 1999;Hõ rak et al 2002;Labocha et al 2004). Thus, variation among individuals may be determined by several factors at the same time.…”
mentioning
confidence: 99%